Hubungan Motivasi Belajar dengan Hasil Belajar Siswa pada Pembelajaran Tematik di Kelas IV Sekolah Dasar - Asmelia, Sherly Putri; Fitria, Yanti (Universitas Negeri Padang, 2022)
The research aim to know there is or no correlation motivation in learning with student learning outcomes in thematic learning of four grade of primary school on cluster two in subdistrict Enam Lingkung regency Padang Pariaman. This type of research is quantitative research with correlation research methods. The amount of sample is 26 students, four grade of primary school 16 Enam Lingkung. The result of the research there is positive correlation an significant students motivation in learning with student learning outcomes in thematic learning of four grade of primary school on cluster two in subdistrict Enam Lingkung regency Padang Pariaman. This was proven from rhitung = 0.533 > rtabel = 0.404, and significance value 0.000 < 0.005. which means that Ha is accepted and Ho is rejected , so the hypothesis says